Nitrogen accumulation, translocation, postanthesis uptake and utilization efficiency under different tillage systems and fertlizer types - Golik, Silvina Inés; Chidichimo, Hugo Oscar; Pérez, Diego; Pane, Luciano (Pesquisa Agropecuaria Brasileira, 2003)
The objective of this work was to analyse N accumulation, translocation, postanthesis uptake and utilization efficiency under two tillage systems (moldboard plow and chisel plow) and different fertilizer types in two cultivars of bread wheat (Buck Pronto and Buck Charrúa). The N fertilizer treatments were: without N, 90 kg ha-1 at sowing as urea, 90 kg ha-1 at sowing as ammonium nitrate, 45 kg ha-1 at sowing and 45 kg ha-1 at tillering as urea and 45 kg ha-1 at sowing and 45 kg ha-1 at tillering as ammonium nitrate. Difference in N accumulation between tillage systems (chisel accumulated 18 kg ha-1 more than moldboard) was found, but this did not correspond to improvement of grain N content by remobilization or by postanthesis N uptake. Fertilization, independently of the type and time of application, increased N accumulated (50 kg ha-1 in average) and N remobilized to the grain, but N contribution to grain arising from postanthesis uptake did not improve. Cultivars presented differences in N accumulated and in N contribution to grain by remobilization and postanthesis uptake. Nitrogen utilization efficiency depended on the tillage systems and the fertilization treatments.